Economic-Social Interaction during Chinas Transition - Assar Lindbeck (Research Institute of Industrial Economics (IFN), 2006)
I discuss the nature of the economic reforms in China during the last quarter of a century in the context of a typology of economic systems, emphasizing the interaction between economic and social mechanisms. I also consider Chinas options for further reforms. I focus on economic reforms that make the growth path less resource demanding and social reforms that enhance income security and improve education and health care for disadvantaged population groups.
Keywords: I18; I19; I38; O53; P30; 330; China; Transition Economies; Social Insurance; Human Services; Systemtransformation; Wirtschaftsreform; Sozialer Wandel; Sozialpolitik; Sozialer Dienst; China